An engineering-based approach for design and fabrication of a customized nasal prosthesis. (October 2015) - Neto, Rui; Costa-Ferreira, António; Leal, Nuno; Machado, Margarida; Reis, Ana
Background and aim: Facial defects (from neoplasms, trauma, etc.) can be functionally and emotionally devastating. A non-invasive treatment for these defects is the application of external prostheses. Conventionally, these prostheses are fabricated by an anaplastologist through a manual procedure, which is an expensive and time-consuming approach. Current advances in computational and engineering tools report an improvement in design and manufacturing of silicone prostheses. This demand motivated this study that aims to develop a methodology for fabricating customized nasal prostheses. Technique: In this study, an 80-year-old woman with a total defect of the nose is considered as case-study. The proposed methodology entails six tasks: (a) data acquisition, (b) three-dimensional reconstruction, (c) prosthesis design, (d) moulds fabrication, (e) prosthesis manufacturing and (f) final fittings. Discussion: The presented approach showed encouraging outcomes since it saves time, reduces costs and allows the achievement of prosthesis with the minimum contact and discomfort to the patient, disclosing excellent aesthetic and functional results. Clinical relevance: Custom-made nasal prostheses with minimum contact and discomfort for the patient can be achieved using an engineering approach based on digital technologies and additive manufacturing that is cost-effective and less time-consuming than the manual procedure.